1998
DOI: 10.1073/pnas.95.11.6037
|View full text |Cite
|
Sign up to set email alerts
|

Stepwisein vitroaffinity maturation of Vitaxin, an αvβ3-specific humanized mAb

Abstract: A protein engineering strategy based on efficient and focused mutagenesis implemented by codon-based mutagenesis was developed. Vitaxin, a humanized version of the antiangiogenic antibody LM609 directed against a conformational epitope of the ␣ v ␤ 3 integrin complex, was used as a model system. Specifically, focused mutagenesis was used in a stepwise fashion to rapidly improve the affinity of the antigen binding fragment by greater than 90-fold. In the complete absence of structural information about the Vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 33 publications
2
106
1
Order By: Relevance
“…Although these strategies can result in significant affinity enhancement, none comprehensively interrogate all six CDR positions in a precise and informative fashion. Other stochastic methods used for maturation (21,23) are also limited because of the inherent randomness in such mutagenesis strategies. Although improved properties might be obtained through these methods, a directed, rational, and informative method based on chemical principles should yield vastly improved variants and informative results about the binding site architecture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these strategies can result in significant affinity enhancement, none comprehensively interrogate all six CDR positions in a precise and informative fashion. Other stochastic methods used for maturation (21,23) are also limited because of the inherent randomness in such mutagenesis strategies. Although improved properties might be obtained through these methods, a directed, rational, and informative method based on chemical principles should yield vastly improved variants and informative results about the binding site architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous protein engineering and mutagenesis strategies have been used for the enhancement of antibody affinity (3,5,6,11,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). For small regions (Ͻ8-10 aa), saturation mutagenesis is typically used to produce all combinations of the 20 naturally occurring amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…In the subsequent Phase I clinical trial [Gutheil et al, 2000], Vitaxin I has been proven safe for therapeutic use, however, it had limited efficacy in patients with advanced malignancies. The affinity of this antibody was further increased using stepwise maturation with phage expression libraries [Wu et al, 1998]. The resulting antibody was named Abegrin (Vitaxin II, MEDI-522), which was later licensed to MedImmune, Inc. (Gaithersburg, MD).…”
Section: Integrin α V β 3 Inhibitorsmentioning
confidence: 99%
“…[6][7][8][11][12][13][14][15] Etaracizumab (Abegrin or MEDI-522; MedImmune, Gaithersburg, Md) is an IgG1 humanized monoclonal antibody engineered from the murine monoclonal LM609, an antibody directed against a conformational epitope of alpha v beta 3 (a v b 3 ) integrin that is present on the surface of certain types of invasive tumor cells, angiogenic endothelial cells, and mature osteoclasts. 16 Although it is expressed at low levels in most normal tissues, a v b 3 integrin is highly expressed in certain malignancies, such as melanoma, late-stage glioma, and renal cell carcinoma, as well as a limited number of cell types, such as endothelial cells involved in angiogenesis and mature osteoclasts involved in bone resorption. [17][18][19][20][21] Preclinical studies using a v b 3 antagonists have reported inhibition of melanoma tumor growth independent of its antiangiogenic effects.…”
mentioning
confidence: 99%